Homogamy in Gender Role Attitudes Among Young Couples: Evidence from Germany - Ansgar Hudde (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
Romantic partners' similarity in gender role attitudes affects important outcomes such as sharing of housework, relationship stability, or fertility. However, there is little knowledge about how similar romantic partners are in these attitudes. Using dyadic panel data from German couples (sourced from pairfam), this study puts the degree of homogamy in gender role attitudes among young couples into perspective by comparing real couples with two types of counterfactuals. To create these counterfactuals, I~re-mate couples in two ways: (a)~randomly and (b)~in such a~way that similarity in attitudes between partners is maximized. Real couples differ only slightly from randomly mated couples, which suggests rather weak attitudinal similarity. Using longitudinal information, I~further test the mechanisms that determine the degree of homogamy: there is strong evidence for alignment over time and for lower rates of separation among homogamous couples, but no evidence for homogamy as a~by-product of assortative mating on other variables. This paper offers methodological and substantial contributions to the literature: it presents a~method for intuitive assessment of the degree of homogamy with multiple variables simultaneously. It also shows that in Germany, macro-level diversity in attitudes largely translates into dissimilar attitudes between partners—with important implications for relationship dynamics.
Keywords: 300; Gender ideology; Mating; Assortative mating; Homogamy; Partner market; Gender revolution; Geschlechterideologie; Partnerschaft; Assortative Mating; Homogamie; Partnermarkt; Gender Revolution